Numeracy skills learning of children in Africa:—Are disabled children lagging behind? - Zhang, Huafeng; Holden, Stein T. (PLOS ONE, 2023)
Significant progress has been achieved in universal basic education in African countries since the late 1990s. This study provides empirical evidence on the within- and across-country variation in numeracy skills performance among children based on nationally representative data from eight African countries (DR Congo, The Gambia, Ghana, Lesotho, Sierra Leone, Togo, Tunisia, and Zimbabwe). We assess whether and to what extent children with disabilities lag in numeracy skills and how much it depends on their type of disabilities. More specifically, we explore whether disabled children benefit equally from better school system quality. The assessment is analysed as a natural experiment using the performance of nondisabled children as a benchmark and considering the different types of disabilities as random treatments. We first evaluate the variation in average numeracy skills in the eight African countries. They can roughly be divided into low- and high-numeracy countries. We apply Instrumental Variable (IV) methods to control the endogeneity of completed school years when assessing subjects’ school performance and heterogeneous disability effects. Children with vision and hearing disabilities are not especially challenged in numeracy skills performance. The low numeracy skills among physically and intellectually disabled children are mainly attributable to their limited school attendance. Children with multiple disabilities are constrained both by low school attendance and by poor numeracy skills return to schooling. The average differences in school performance across the high- versus low-numeracy skill country groups are larger than the within-group average differences for disabled versus non-disabled kids. This indicates that school enrolment and quality are crucial for children’s learning of numeracy skills, and that disabled children benefit equally from better school quality across these African countries.

In-service Zimbabwean teachers obstacles in integrating ethnomathematics approaches into the teaching and learning of geometry - Sunzuma G.; Maharaj A. (Journal of Curriculum Studies, 2021)
For teachers to integrate ethnomathematics approaches, it is essential to understand their views related to the implementation challenges of such approaches. In schools, teachers held previous views and experiences that influenced their integration of ethnomathematics approaches. This study investigates school-related factors that impede the integration of ethnomathematics approaches into the teaching and learning of geometry as well as suggesting possible solutions into mathematics instruction in Zimbabwe. A convergent mixed methods design, using questionnaires, focus group discussions and interviews, was used. Stratified random sampling, research-based recruitment and purposive sampling were used to select 42 participants. Inductive analysis was used to analyse qualitative data and descriptive statistics was employed to analyse quantitative data. The study revealed that curriculum-related challenges, insufficient resources such as textbooks and very few cultural examples and activities affect the integration of ethnomathematics approaches into the teaching and learning of geometry. There is a need for curriculum developers to engage more teachers during the curriculum design in order to develop material that suits all the learners in Zimbabwe. 2020 Informa UK Limited, trading as Taylor & Francis Group.
Keywords: Learning outcomes; Mathematics education; Primary education; Secondary education; Teaching methods; _C:Zimbabwe; _authorsString:Second,A.B.; _checkedWith:AERD; _research:Mixed methods; _type:Peer-reviewed article

Shona Mathematical Instructional Practices in Bilingual Primary Schools in Zimbabwe - Chikodzi M.I., Kaino L.M. (2020)
Many Zimbabwean mathematics classrooms have student populations from diverse cultural backgrounds who speak diverse Shona dialects. Most of the mathematics teaching is not related to the learners world or everyday experiences because it is taught in English, a second language for most of these learners. Teachers therefore play a fundamental role in making sure that learners in this bilingual setup understand the mathematical concepts being taught. The debate on whether English or indigenous languages are suitable for use in education is increasing. This paper explores possible instructional practices to assist bilingual learners. A qualitative approach was used to explore the instructional practices used by primary school teachers during the teaching and learning of mathematics in Zimbabwe. The findings indicated that teachers code-switched between English and Shona and also used examples from the learners environment. It was concluded that there was a possibility of using a bilingual model including Shona and English when teaching mathematics to bilingual learners. The idea is to create a caring, colourful, exciting, stimulating, and reflective environment as a way of engaging learners even if they are from diverse cultural and social backgrounds. The latter would also reduce marginalisation of bilingual learners. 2021 Unisa Press.
Keywords: Mathematics education; Primary education; _C:Zimbabwe; _authorsString:Single/Second,First; _checkedWith:AERD; _research:qualitative; _type:Peer-reviewed article

Barriers to Mathematics Teachers Use of Their Knowledge of Students Learning Styles in Mathematics Teaching: A Case of Secondary Schools in Zimbabwe - Mangwende E., Maharaj A. (2020)
This qualitative research study explored barriers that impinged on teachers use of their knowledge of students learning styles in teaching mathematics. It was a case study of three secondary schools in the Makoni District of Manicaland Province in Zimbabwe. Participants were fifteen mathematics teachers. Results revealed that the barriers were related to the teachers, the students, the curriculum and the socio-economic status of the schools. Collaborative teaching, formation of mathematics clubs, mobilisation of resources, use of excursions and in-servicing of teachers were recommended as ways of reducing the effects of the barriers. 2020. All rights reserved.
Keywords: Mathematics education; Secondary education; Teacher capacity; Teacher education; _C:Zimbabwe; _authorsString:Single/Second,First; _checkedWith:AERD; _research:qualitative; _type:Peer-reviewed article